2024
DOI: 10.11591/ijeecs.v33.i2.pp1293-1301
|View full text |Cite
|
Sign up to set email alerts
|

An efficient smart grid stability prediction system based on machine learning and deep learning fusion model

Annemneedi Lakshmanarao,
Ampalam Srisaila,
Tummala Srinivasa Ravi Kiran
et al.

Abstract: <span>A smart grid is a modern power system that allows for bidirectional communication, driven mostly by the idea of demand responsiveness. Predicting the stability of the smart grid is necessary for improving its dependability and maximizing the efficacy and regularity of electricity delivery. Predicting smart grid stability is difficult owing to the various elements that impact it, including consumer and producer engagement, which may contribute to smart grid stability. This research work proposes mac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Previous studies have identified gaps in addressing the challenges faced by the tourism industry. For instance, inadequately trained personnel and skills gaps hinder effective accommodation of foreign visitors [6]. Furthermore, existing augmented reality (AR) systems have limitations in accurately recognizing and tracking real-world objects and patterns [7]- [9].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have identified gaps in addressing the challenges faced by the tourism industry. For instance, inadequately trained personnel and skills gaps hinder effective accommodation of foreign visitors [6]. Furthermore, existing augmented reality (AR) systems have limitations in accurately recognizing and tracking real-world objects and patterns [7]- [9].…”
Section: Introductionmentioning
confidence: 99%